BELAJAR ARITMETIKA MENGGUNAKAN BUAH COKLAT - Dubi Ardiansyah; Chika Rahayu (STKIP Weetebula, 2020)
The purpose of this service is to determine the effectiveness of the Contextual Teaching and Learning learning model in social arithmetic material on student learning outcomes. This service uses a pretest posttes design. Data collection uses documentation and test methods. The data is processed using the t test statistical test. Based on data analysis, the average experimental class students were 75.75 and the control class was 60. From the average value data obtained by students, it can be seen that mathematics learning uses the Contextual Teaching and Learning (CTL) learning model with fruit context. Chocolate is effective on student learning outcomes in social arithmetic material..Keywords: Efektiveness, Contextual Teaching and Learning, learning outcome.